Grafting of a new bis-silylamido aluminum species on silica: insight from solid-state NMR into interactions with the surface. Issue 16 (29th March 2019) - Vancompernolle, Tom; Merle, Nicolas; Capet, Frédéric; Del Rosal, Iker; Laurent, Maron; Delevoye, Laurent; Pourpoint, Frédérique; Gauvin, Régis M.
Abstract : The structure of silica-supported aluminum amides has been investigated through combined MAS NMR and DFT investigations, highlighting metal–support interactions. Abstract : The new bisamido aluminum species [AlCl{N(SiMe3 )2 }2 (THF)] (1 ) was prepared and fully characterized by 27 Al and 35 Cl solid-state NMR, along with X-ray diffraction studies.1 was grafted on silica partially dehydroxylated at 700 °C, affording silica-supported Al species. The resulting material (2 ) was characterized by IR, elemental analysis and 1 H, 13 C and 27 Al solid-state MAS NMR. The 1D and 2D 27 Al MAS NMR studies showed the occurrence of two types of species, where the Al center adopts a tetracoordinated coordination sphere, with as an additional coordinated Lewis base, either a THF ligand or a silica-surface siloxane moiety. DFT calculations allowed understanding the grafting mechanism and the spectroscopic properties of the material.